Built-in fast gather control network for efficient support of coherence protocols - Lodde, Mario; Roca, Toni; Flich, José (Chronic diseases and translational medicine, 2013)
Future chip multiprocessors will include hundreds of cores organised in a tile-based design pattern. These systems commonly employ a shared memory programming model, thus needing a coherence protocol to keep data consistent on the various levels of the cache hierarchy. Usually an invalidation-based protocol is used, where shared copies are invalidated before a write operation. In this study, the authors propose a NoC re-organisation in which a small and fast dedicated control network is used to transmit acknowledgement messages related to the invalidation process, thus relieving the NoC from a considerable percentage of traffic. The dedicated control network is evaluated both with full map directories and with a broadcast-based protocol (Hammer). Experimental evaluation shows significant gains in performance. With a low area overhead (<2.5%), the control network reduces NoC traffic and miss latency, thus reducing execution time up to 16%. Simulation results show a reduction of network traffic up to 80% and a reduction of store and load miss latency up to 70 and 40%, respectively.